2017
DOI: 10.1016/j.jhep.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity for rs738409:G in PNPLA3 is associated with increased mortality following an episode of severe alcoholic hepatitis

Abstract: Background & Aims: Carriage of rs738409:G in PNPLA3 is associated with an increased risk of developing alcohol-related cirrhosis and has a significant negative effect on survival. Short-term mortality in patients with severe alcoholic hepatitis is high; drinking behaviour is a major determinant of outcome in survivors. The aim of this study was to determine whether carriage of rs738409:G has an additional detrimental effect on survival in this patient group. Methods: Genotyping was undertaken in 898 cases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…Multiple studies found relationships of PNPLA3 I148M with NAFLD, but reported associations with mortality from liver disease or all causes are limited. In the Study of Health in Pomerania in North‐Eastern Germany, 148M was associated with a 4‐fold increase in the liver disease mortality hazard for men only, most likely attributable to small sample size, shorter follow‐up time, and fewer events in women . In another report, 148M homozygosity doubled the risk of hepatic decompensation and liver disease mortality in patients with FLD‐associated portal hypertension .…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies found relationships of PNPLA3 I148M with NAFLD, but reported associations with mortality from liver disease or all causes are limited. In the Study of Health in Pomerania in North‐Eastern Germany, 148M was associated with a 4‐fold increase in the liver disease mortality hazard for men only, most likely attributable to small sample size, shorter follow‐up time, and fewer events in women . In another report, 148M homozygosity doubled the risk of hepatic decompensation and liver disease mortality in patients with FLD‐associated portal hypertension .…”
Section: Discussionmentioning
confidence: 97%
“…Infection‐related biomarkers like pretreatment serum lipopolysaccharide, bacterial DNA, high‐sensitivity C‐reactive protein, and procalcitonin are associated with the risk of infection and 90‐day mortality . Furthermore, as mentioned previously, the presence of SIRS at admission, with or without infection, predicts multiorgan failure (especially AKI) and early death . Although the recovery of liver function in short‐term prognosis is paramount and captured by the previously discussed prognostic models, in the long term, abstinence from alcohol is the main driver of outcome in patients with severe AH surviving beyond 6 months .…”
Section: Diagnosis and Treatment Of Alcohol‐associated Liver Diseasesmentioning
confidence: 89%
“…Genetic variants have been associated with differential risk of ALD. Patatin‐like phospholipase domain‐containing protein 3 ( PNPLA3 ) polymorphism has been associated with risk of AC and AH, as have polymorphisms in the transmembrane 6 superfamily member 2 ( TM6SF2 ) , and membrane bound O‐acyltransferase domain‐containing 7 ( MBOAT7 ) genes . PNPLA3 and TM6SF2 polymorphisms are also associated with increased risk of HCC in ALD .…”
Section: Pathophysiology and Risk Factors For Alcohol‐associated Livementioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients in our study was too small to assess the efficacy of ciprofloxacin therapy on the survival of the patients. A recent study has shown an association between rs738409:G homozygosity in PNPLA3 and medium‐term mortality in severe AH (Atkinson, Way, McQuillin, Morgan, & Thursz, ). There were no rs738409:G homozygotes among our patients, and heterozygosity was not related to short‐term mortality.…”
Section: Discussionmentioning
confidence: 99%